A damped simultaneous iterative method for split equality problems of asymptotically demi-contractive mapping in the intermediate sense without prior knowledge of operator norms. Issue 4 (3rd July 2016) - Che, Haitao; Li, Shoujin
Abstract: In this article, we propose a damped simultaneous iterative algorithm with a way of selecting the step sizes which does not need any priori information about the operator norms. The sequences generated by the algorithm weakly converge to a solution of split equality problem of asymptotically demi-contractive mapping in the intermediate sense is proved. Preliminary numerical results indicate the feasibility and efficiency of the algorithm.